Enhanced Urea Oxidation Reaction Through Layered Double Hydroxides: Insights From ZIF‐67‐Derived Nanostructures - Yuri Jeon; Jury Medvedev; Yeeun Seong; Xenia Medvedeva; Cheongwon Bae; Jeongeon Kim; Anna Klinkova; Juyeong Kim (EcoMat)
ABSTRACT Layered double hydroxides (LDHs) are ionic layered compounds characterized by anion‐containing intermediate regions within positively charged brucite‐like layers. LDHs have shown high electrochemical activity in energy conversion systems such as batteries and fuel cells. In this study, we developed a hierarchically porous nanostructure derived from zeolitic imidazolate framework‐67, which was subsequently transformed into an LDH structure with varying Ni concentrations. We precisely controlled the Ni‐to‐Co ratio within the LDH structure and investigated how different mole fractions of Co and Ni influence catalytic activity and selectivity for the electrochemical urea oxidation reaction (UOR). LDH structures with low Ni content (up to 40%) demonstrated high activity and selectivity for O2 due to their structural instability and the predominant oxygen evolution reaction (OER) originating from ZIF‐67. In contrast, LDHs with high Ni content (over 60%) supressed OER and exhibited enhanced activity for UOR. The resulting hollow structure with an expanded electrochemically active surface in LDHs with high Ni content could improve mass transport and diffusion at the electrode interface, leading to better reaction kinetics and higher current densities. These findings provide a foundational design guideline for metal–organic framework‐derived nanostructure in UOR.